Effect of Temperature on Precipitation Rate of Calcium Carbonate Produced through Microbial Metabolic Process of Bio Materials - Prima Yane Putri; Keiyu Kawaai; Isao Ujike; Saya Yamamoto (Institute of Research and Community Outreach - Petra Christian University, 2016)
Concrete is the most widely used construction material in civil engineering. But plain concrete is a brittle material and has little resistance to cracking. The cracking in concrete promotes deterioration such as the corrosion of reinforcing rebar, therefore, repair in filling the crack is often carried out. Recently, repair methods using bio-based materials associated with microbial metabolic processes leading to precipitation of calcium carbonate have been intensively studied. In this study, influencing factors on the precipitation rate depending on the constituents of bio-based material comprising yeast, glucose and calcium acetate mixed in tris buffer solution was examined for improving the rate of initial reactions. In addition, effect of temperature change on the amount of calcium carbonate precipitation was also investigated. The precipitates were identified by X-ray diffraction. It was shown that the increase of temperature lead to a change on calcium carbonate precipitation and caused the pH decrease under 7.0.